Fibrinolytic Changes in Women with Preeclampsia. (October 2022) - Godtfredsen, Anne Cathrine; Sidelmann, Johannes Jakobsen; Dolleris, Britta Blume; Jørgensen, Jan Stener; Johansen, Emma Kathrine Jungjohan; Pedersen, Melissa Fernard Bøg; Palarasah, Yaseelan; Gram, Jørgen Brodersen
Objectives: Preeclampsia (PE) is a serious complication of pregnancy. The fibrinolytic system play crucial roles regarding placentation and evolution of PE. Aim: To study comprehensively components of the fibrinolytic system and fibrin lysability in women with PE. Design and Methods: 117 women with PE and matched controls were included. Tissue type plasminogen activator (t-PA), plasminogen, PAI-1, plasmin inhibitor (PI), D-dimer, the fibrinolytic potential of dextran sulphate euglobulin fraction (DEF), PAI-2, polymere PAI-2, fibrin clot lysability, thrombin activatable fibrinolysis inhibitor (TAFI) and fibrinogen were assessed. Results: Women with PE had significantly increased concentrations of t-PA and PAI-1, whereas the plasma concentration of PAI-2 was significantly lower compared to controls, p < 0.0001. Polymere PAI-2 was detected in both groups. DEF, TAFI and fibrinogen were not different between the groups. D-dimer was significantly increased and plasminogen/PI together with fibrin clot lysability time decreased in the PE-group, p  =  0.0004 p  =  0.04, p  =  0.03, p < 0.0001 respectively. Conclusion: This study demonstrates that PE is associated with an affected t-PA/PAI-1 system, decreased PAI-2 and increased fibrin lysability. Furthermore, PAI-2 has the potential to polymerize during pregnancy.